2015
DOI: 10.1016/j.jneuroim.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of auto-antibodies to DAT in the serum: Interactions with DAT genotype and psycho-stimulant therapy for ADHD

Abstract: ADHD patients were assigned, according to severity, either to a non-pharmacological therapy (NPT, N=32) or to a pharmacological treatment (PT, N=14) with methylphenidate (MPH). In ADHD children, blood samples were withdrawn twice, at recruitment (T0 basal) and after 6 weeks (T1); following 16 excluded subjects, DAT genotype was characterized (9-repeat or 10-repeat alleles; N=15 each). After 18 months of NPT or PT, some patients (carrying at least one 9-repeat allele) were blood sampled again (T2), for comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…These results have been replicated in a following study [44], and the authors also demonstrated that ADHD patients had increased serum levels of interleukin 6 (IL-6) and IL-10. Increased levels of antibasal ganglia antibodies [45] and antibodies against the dopamine transporter [46] have also been detected in ADHD, supporting the role of the immune system in the disorder.…”
Section: Biochemical Markersmentioning
confidence: 85%
“…These results have been replicated in a following study [44], and the authors also demonstrated that ADHD patients had increased serum levels of interleukin 6 (IL-6) and IL-10. Increased levels of antibasal ganglia antibodies [45] and antibodies against the dopamine transporter [46] have also been detected in ADHD, supporting the role of the immune system in the disorder.…”
Section: Biochemical Markersmentioning
confidence: 85%
“…McGough et al () and Zeni et al () found no significant association between specific genes and occurrence of adverse events. Except two studies (Giana et al, ; Kirley et al, ), other researchers reported the acceptability of MPH as more than 90% (mean: 97.2%).…”
Section: Resultsmentioning
confidence: 92%
“…To the best of our knowledge, our meta‐analysis was the first to investigate 9R homozygosity in response to MPH among children with ADHD. Moreover, greater number of studies on children are now available (Giana et al, ; Hong et al, ; Kim, Sharma, & Ryan, ; Pasini et al, ; Ray et al, ; Stein et al, ). Apparently, a review of more recent studies is required to enhance the existing knowledge and clarify the observed inconsistencies regarding the association between the SLC6A3 VNTR and clinical response to MPH in children with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…These findings link post infectious autoimmunity to the onset of both OCD and ADHD. Giana et al found elevated IgG autoantibody titers against DAT in the serum of ADHD children by ELISA (n = 61) [153], which again suggests that the dysregulation in the levels of dopamine neurotransmitter may be caused by autoantibodies in these disorders.…”
Section: Obsessive-compulsive Disorder (Ocd) and Attention-deficit/hymentioning
confidence: 97%